THE IMPLEMENTATION OF TONGUE TWISTERS TO IMPROVE THE STUDENTS’ ABILITY TO PRONOUNCE FRICATIVE CONSONANTS AND LONG VOWELS - Maulida, Lailatul (Journal of English Teaching and Learning Issues, 2018)
The main factor of failure in mastering speaking encountered by the eighth grade students of SMP Ma’arif 1 Ponorogo  in the academic year of 2014/21015 was dealing with pronunciation. The research was classroom action research that was conducted in two cycles with planning, acting, observing, and reflecting as the stages done in each cycle. The data were collected from the pre-test, test 1 and post-test as the quantitative data and from interviews, observation, and field note as the qualitative data. The data were analyzed by comparing the score of pre-test, test 1 and post-tests and by using interactive model method. The findings showed that the implementation of tongue twister as a teaching technique could improve the students’ pronunciation of fricative consonants and long vowels. In addition, it can be concluded that tongue twisters is an appropriate technique for teaching speaking, especially pronunciation.